Low-cost Apartment Program Implementation in Surabaya Metropolitan Area. (2015) - Rachmawati, Farida; Soemitro, Ria A.A.; Adi, Tri Joko W.; Susilawati, Connie
Abstract: The low-cost apartment development program is one of the reliable solutions to reduce housing backlog in East Java Province due to land scarcity and high price of land. There are some supporting regulations concerning low-cost apartment management and implementation. But in some aspects, existing low-cost apartment program implementation does not meet the regulation and inhabitant's need. The objectives of this research are to compare the low-cost apartment regulation and real implementation in Surabaya Metropolitan Area and to generate improvement strategies. The regulation and technical standard variables were obtained from literature review studies. The comparison parameters to better understand the low-cost apartment implementation were then observed to purposive sampling respondents from management team and 221 random sampling respondents from inhabitants. These unconformity variables were then identified and analyzed using descriptive statistic. The result shows that some problems between regulation and real implementation are associated with rental price, inhabitant segmentation, maintenance program, location and building technical standards. Some strategies for the better implementation according to the inhabitant's need and regulation are inhabitant segmentation from low-income groups, limitation in occupancy, partnership initiation with private sector who wants to provide the housing for their employee in their land, rental price adjustment and better coordination between institutions.